Atypical Disseminated Variant of Galli–Galli Disease: A Review of the Literature. (July 2020) - Yang, Anes; Cheung, Karen; Kossard, Steven; Murrell, Dedee F.
Abstract : Abstract: Galli–Galli disease (GGD) is a rare genodermatoses within the group of reticulated pigmentary disorders of the skin. Traditionally, its clinical presentation is identical to that of Dowling–Degos disease (DDD), with the additional feature of acantholysis on histopathological examination. We have reviewed the published cases of GGD to provide further support for the hypothesis that in fact, 2 phenotypes of GGD exist: the characteristic flexural GGD associated with KRT5 mutations and a disseminated variant with no mutation identified to date. A review of the literature revealed 53 reported cases of GGD. Fifteen atypical phenotype cases are described, and no KRT5 mutation has yet been identified. There is growing evidence that acantholysis is an underreported feature of DDD and that GGD and DDD are variations of the same disease, or in fact the same entity. This theory is supported by the identification of the c.418dupA missense mutation in both GGD and DDD. This review highlights that there is growing evidence that there are likely 2 clinical phenotypes of GGD with an associated genotypic correlation.